Ethereum blockchain-based three factor authentication and multi-contract access control for secure smart home environment in 5G networks - Atiewi S.; Al-Rahayfeh A.; Almiani M.; Abuhussein A.; Yussof S. (Springer, 2025)
With the rapid advancement of technology, smart home environments have become increasingly popular, offering convenience and automation to homeowners. However, as these smart homes become more interconnected and integrated into 5G networks, security concerns arise, especially with the potential for unauthorized access and control. To address these security challenges, this research proposes a novel Robot Operating System based Ethereum blockchain (ROS-EB) that is responsible for secure and private data storage. In this research we reduce high complexity. The registration contract is performed by a certificate authority, and the key is generated using the Enhanced Elliptic Curve Digital Signature (EECDS) algorithm which improves the secure and private communication between the users, IoT devices, and edge-gateway. To increase security, we perform secure authentication by creating an effective methodology based on the Touch Well before Use (TWU) method which protects against attacks. The Adaptive Neuro-Fuzzy Inference System (ANFIS) is used for role-based access control and judge contracts. To improve secure service providing, we perform the detection of malicious and vulnerable users using Improved Cuckoo Optimization and Support Vector Machine (ICO-SVM) and Gated Recurrent Unit and Residual Neural Network (GRU-ResNNet) algorithm in ROS-EB which reduces the vulnerability in the smart home. For improving QoS, we have provided sufficient security service in the smart home environment (i.e. adjusting temperature, turning on/off lights, adjusting watering system and mantrap) by using multi-contract. The performance metrics such as Communication delay, register contract, access contract, detection time, and Energy consumed were assessed. ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.